Designation of Soap Molder Machine and Procedure for Transparent Soap - Mat Sharif Z.B.; Mohd Taib N.B.; Bin Yusof M.S.; Bin Rahim M.Z.; Mohd Tobi A.L.B.; Bin Othman M.S. (Institute of Physics Publishing, 2023)
Condensed matter physics; Industrial engineering; Materials science; Soaps (detergents); Air bubbles; Production rates; Production time; Soap production; Soap solution; Transparent soap; Engineering